LITERATUR REVIEW : HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN TUBERKULOSIS DI LEMBAGA PEMASYARAKATAN TANGERANG TAHUN 2020 - Winarni, Lastri Mei (Jurnal Surya, 2020)
Background: Tuberculosis is a lung disease caused by Mycobaterium tuberculosis. places where the spread of tuberculosis is easy, namely in prisons because of poor sanitationObjectives: to determine the incidence of TB in prisons regarding environmental sanitationDesign: The research method used in this study is the method of searching journal article in a database by using the word keyword according to topic.Data Sources Results: The results of this study the author discusses the weaknesses and strengths of this journal by using a SWOT analysis. Strength was found in several prisons that had screened for TB and implemented the DOTS (Directly Observed Treatment Shortcourse) strategy. Weakness has not conducted direct research, researchers only review studies that have been conducted by previous researchers. Prison opportunities can inform the importance of maintaining a clean environment and health so as not to be infected by previous TB sufferers. Threats If the prison authorities are not firm in providing information to prisoners in providing counseling, it is feared that the incidence of TB in prisons will increase due to the uncontrolled influence of environmental sanitation.Conclusion: showed that there werw still many person that still did not meet environmental requirements and were still carrying out bad behavioral habits such as smoking habits, habitual salivation and not keeping their mouths shut when coughing/not wearing masks. Causing a high incidence of tuberculosis in prisons